The role of control in precipitating and motivating self-harm in young people: A systematic review and meta-synthesis of qualitative data - Demee Rheinberger; Aimy Slade; Biya Tang; Ashley Hoye; Hiroko Fujimoto; Wu-Yi Zheng; Glenn Holmes; Katherine Boydell; Alison L. Calear; Helen Christensen; Samantha Tang (PLoS ONE, 2025)
The last decade has seen a steady rise in self-harm rates in young people in developed countries. Understanding the experience of self-harm in young people can provide insight into what may be driving this increase. The aim of the current review was therefore to synthesise qualitative research examining precipitating and motivating factors underlying self-harm in young people. PsychInfo, Embase and Medline were systematically searched for articles published up to September 2024. A total of 50 qualitative studies (study N ranging from 3–115) were identified, and key findings were synthesised using Attride-Stirling’s Thematic Network Analysis process. The quality of included studies was assessed using a modified version of two Joanna-Briggs Institute Checklists. Control was identified as a global theme. Precipitants were informed by young people’s perception of an absence of control and the desire to gain control was identified as an underlying motivation for self-harm. The findings from this review highlight the need to support and educate young people to improve their distress tolerance, particularly in respect to situations outside of their control. Furthermore, therapeutic interventions, and training and educational programs targeting young people who self-harm and their family members might be effective interventions for self-harm in young people.